Statcom integration in a power grid to enhance voltage stability - Isselem Arbih Ethmane; Ahmed Yahfdhou; A.K. Mahmoud; M Maaroufi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
To solve load growth of an existing electrical system, we at first inject the power in system by building new electrical plants as wind, solar or thermal. And secondly in year 2030, when the system is so meshed, some customers are far away at production stations. We propose the installation of FACTS devices to enhance voltage in stability margins of power system under study. The power flow analysis using Newton Raphson method was running on Matlab and PSS/E Simulator. The results of simulation without STATCOM show the most affected buses. To improve the voltage for all these buses, reduce the power mismatches and tranmit more ative power, we insert STATCOM. STATCOM is a shunt connected FACTS application which facilitate the fast voltage control, the reactive power control and reduce the harmonics in a power system.